Internet connectivity disruption in Azerbaijan (Azerbaijan) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Azerbaijan. Data sourced from IODA.
Network Disruption Incident ID: AZ-2026-0091. Severity: critical. Confidence: 70%